The evaluation by passes energy based on in vitro gas production digestibility and palatability - Dewi, R.R.; Muhlisin, Muhlisin; Kustantinah, Kustantinah (2021)
The purpose of this study was to evaluate the influence of combined treatments of the fish oil protected with different NaOH concentration and drying method as bypass energy based in vitro total gas production and palatability. Lemuru fish oil, starch and NaOH were used for capsulation and optimizing saponification, along with CaCl2 and required reagents were used for in vitro gas test. The indicators for protected fish oil palatability test were 18 female lamb, aged 7-8 months, with average weight 15.37 Â± 1.09 kg. A completely randomized design was deployed for in vitro gas production with three replications in which different NaOH concentrations and drying methods were applied. Then, to see the results of the animal preference level, it was by reducing the feeding time and feeding residue in 24 hours. All data was analysed using analysis of variance (ANOVA) with Duncan test. As a results, fish oil protected with different NaOH concentration and drying method have no significant effect on total gas production. Furthemore, the results on the palatability analysis showed that there was no significant different in all treatments. Â© Published under licence by IOP Publishing Ltd.